Ab initio molecular dynamics study of the interlayer and micropore structure of aqueous montmorillonite clays - James L. Suter (1369596) (2015)
Ab initio molecular dynamics simulations have been performed to gain an understanding of the interfacial microscopic structure and reactivity of fully hydrated clay edges. The models studied include both micropore and interlayer water. We identify acidic sites through dissociation mechanisms; the resulting ions can be stabilized by both micropore and interlayer water. We find clay edges possess a complex amphoteric behavior, which depends on the face under consideration and the location of isomorphic substitution. For the neutral (110) surface, we do not observe any dissociation on the timescale accessible. The edge terminating hydroxyl groups participate in a hydrogen bonded network of water molecules that spans the interlayer between periodic images of the clay framework. With isomorphic substitutions in the tetrahedral layer of the (110) clay edge, we find the adjacent exposed apical oxygen behaves as a Brönsted base and abstracts a proton from a nearby water molecule, which in turn removes a proton from an AlOH2 group. With isomorphic substitutions in the octahedral layer of the (110) clay edge the adjacent exposed apical oxygen atom does not abstract a proton from the water molecules, but increases the number of hydrogen bonded water molecules (from one to two). Acid treated clays are likely to have both sites protonated. The (010) surface does not have the same interfacial hydrogen bonding structure; it is much less stable and we observe dissociation of half the terminal SiOH groups (SiOH→ SiO− +H+) in our models. The resulting anions are stabilized by solvation from both micropore and interlayer water molecules. This suggests that, when fully hydrated, the (010) surface can act as a Brönsted acid, even at neutral pH. Other Information Published in: Geochimica et Cosmochimica Acta License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.gca.2015.07.013